PENGUKURAN TINGKAT MOTILITAS SPERMA BERDASARKAN LINEARITAS SPERMA MENGGUNAKAN METODE ADAPTIVE LOCAL THRESHOLD DAN ELLIPSE DETECTION - Hidayatullah, Priyanto; Nuriyadi, M.; Awaludin, Iwan; Kusumo, Reyhan Damar (Jurnal Informatika, 2015)
Technology that can be used toassist sperm examination is Computer-Aided Sperm Analysis (CASA). The problems with this technology are expensive and the methods are not open for public. A lot of researches have been done to have an altenative CASA’s method to examine sperm quality accurately, inexpensively, and fast. This research is focused on measuring the level of sperm motility. Visual observations of sperm motility greatly depend on each andrologists which are subjective and also the possibility of repetition for the examined sample does not exist. Moreover, visual observation cannot provide precise values for parameters that affect the sperm motion patterns which are Velocity Straight Line, Velocity Curvilinear Line, and Linearity. Focus of this research is to create an application using sperm detection method, Local Adaptive Threshold and Ellipse Detection to measure sperm linearity to determine the level of sperm motility based on the WHO standard. Experiment produces result with the smallest difference 5.7333% and the biggest difference 10.4667% compared to the result of visual analysis by andrologist.